New handbook of political science - Goodin, Robert E (ed.); Klingemann, Hans - Dieter (ed.) (Oxford, 1996)
The New Handbook of Political Science is an authoritative survey of developments in the discipline compiled by 42 of the most famous political scientists worldwide, analysing progress over the past twenty years and assessing this in the context of historical trends in the field. Discussion of each of the main subdisciplines: political institutions political behaviour comparative politics international relations political theory public policy and administration political economy political methodology breaks down into four sections: an overview of the field analysis from two key perspectives in the field Old and new : an eminent scholar in the field assesses the new developments in the light of older traditions in the discipline International in its scope, systematic in its coverage, A New Handbook of Political Science will become the reference book for political scientists, and those tracking their work, into the next century. This book is intended for university students in political science, from second year undergraduate to postgraduate. Academics lecturing in political science, sociology, law, economics, and philosophy.
Keywords: "Political science handbook, mannual"